The effectiveness of the use of various options for drainage of the abdominal cavity in creating a model of chronic peritonitis and the determination of indicators of total peritoneal fibrosis - A. B. Kebkalo; A. O. Reiti; V. V. Hrianyla; M. O. Kondratiuk (Patologìâ)
For the early diagnosis and prognosis of chronic peritonitis, today there is an urgent need to create an optimal model of chronic peritonitis, to determine the indicators and rates of progression of peritoneal fibrosis.